Prelimenary survey of freshwater snails in selected barangays in the coastal region of Palo, Leyte. - Migue, Nina Angeline R. (Nina Angeline R. Migue, 2018)
Gastropods are soft-bodied, single-valve animals of Phylum Mollusca. It is one of the most diverse taxa including over 40,000 species in which 5,000 of these are snails thriving in freshwater habitats. This study is aimed to provide a preliminary assessment on the freshwater snails in Palo, Leyte. Freshwater snails were collected in three accessible collecting stations within four selected barangays through intensive snail search and random ring sampling on March 2018. A total of 3487 freshwater snails were collected in Palo, Leyte. These consisted of 9 species belonging to 6 families. The prosobranchs were comprised of 4 families (Ampullaridae, Neritidae, Thiaridae and Viviparidae, while the other 2 families (Pachychitidae and Planorbidae) were identified to be pulmonates. Pomacea canaliculata (Ampullaridae) was the predominant freshwater snail species, making up to 65% of all individual snails, followed by Melanoides tuberculata. Faunus ater (Pachychilidae) had the lowest snail count. The snail species were found in habitats with moist substratum, organic matter, and vegetation cover. The diversity was relatively low, with H' values ranging from 0.2479 in Intensive Snail Search to 1.189 in Random Snail Search. The low diversity values was influenced by the high abundances and densities of tuberculata, P. canaliculata across all stations due to their invasive nature.